The Effect of Asymmetric Information Towards Tendency of Accounting Fraud (Case Study of West Sulawesi Provincial Government) - Jumardi Jumardi (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of information asymmetry on accounting fraud tendencies in the West Sulawesi provincial government. This type of research uses a quantitative approach. This study uses primary data. Collecting data using questionnaires. The population in this study were government structural officials with the rank of echelon II, echelon III, and echelon IV, totaling 813 people. Sampling used the slovin formula method, so that a sample of 89 was obtained. This study used a simple linear regression analysis approach. The results of the study show that information asymmetry has a positive effect on the tendency of accounting fraud